The Factor Structure of the Autobiographical Memory Test in Recent Trauma Survivors - Griffith, James W. (American Psychological Association, 2012)
The objective of this study was to examine the psychometric properties of the Autobiographical Memory Test (AMT), which is widely used to measure overgeneral autobiographical memory in individuals with depression and a trauma history. Its factor structure and internal consistency have not been explored in a clinical sample. This study examined the psychometric properties of the AMT in a sample of recent trauma survivors (N = 194), who completed the AMT 2 weeks after a trauma. Participants were also assessed with structured clinical interviews for current acute stress disorder and current and past major depressive disorder. Confirmatory factor analysis and item response theory were used to analyze the AMT in the whole sample. The factor structure of the AMT was also compared for (a) individuals with and without lifetime major depressive disorder and (b) individuals with current (posttrauma) major depressive disorder and/or acute stress disorder versus those with neither disorder. In all of these analyses, the AMT with cues of positive and negative valence had a 1-factor structure, which replicates work in nonclinical samples. Based on analyses of the whole sample, scores from the AMT had a reliability estimate of .72, and standard error of measurement was lowest for people who scored low on memory specificity. In conclusion, the AMT measures 1 factor of memory specificity in a clinical sample and can yield reliable scores for memory specificity. More psychometric studies of the AMT are needed to replicate these results with similar and other clinical populations.